Social Democracy and Distributive Conflict in the UK, 1950-2010 - Carlo V. Fiorio; Simon Mohun; Roberto Veneziani (University of Massachusetts, Department of Economics, 2013)
ln the last three decades, two questions have been central for the Left. ls there a future for electoral socialism and social democracy? And, is it any longer possible to promote a significant redistribution of income in favour of labour? Political and economic events seem to suggest negative answers. ln his influential work, Adam Przeworski suggests that this is an irreversible trend that makes it impossible in the long-run to promote genuinely socialist objectives in capitalist democracies. ln particular, the structural dependence of labour on capital severely constrains feasible income distributions. ln this paper, a detailed quantitative and qualitative analysis of the post-war UK economy is provided which casts doubts on the structural dependence thesis. A short run profit-squeeze mechanism seems to exist, but income shares are more variable than the structural dependence argument suggests, and the power resources available to the two main classes in the economy are among the key determinants of distributive outcomes, different political-economic equilibria corresponding to different configurations of the balance of power between the two classes. JEL Categories:
Keywords: D33; E32; J5; 330; social democracy; income distribution; structural dependence thesis